The Effect of Rhizopus sp. Concentration and Fermentation Time on the Characteristics of Country Chicken Egg White Flour - Fakhruzy Fakhruzy; Anwar Kasim; Aswaldi Anwar (Universitas Muhammadiyah Palembang, 2023)
The process of making domestic chicken egg white flour can be done by drying using an oven at 105 0C. To avoid the Maillard reaction, fermentation was carried out with Rhizopus sp. first. In this study, Rhizopus sp. concentrations of 0.2 %, 0.4 %, 0.6 %, 0.8 % and fermentation times of 6 hours, 12 hours and 24 hours were used. The aim of the research was to analyze the effect of the concentration of Rhizopus sp. yeast and the length of fermentation time on the characteristics of the egg white flour produced. The results showed that the concentration of Rhizopus sp. yeast and the length of fermentation time had an effect on the yield of egg white flour (P<0.05). The highest yield was obtained from using a concentration of 0.8 % and a fermentation time of 24 hours, namely 14.40 %. The lowest water content value was obtained from using a concentration of 0.2 % and a fermentation time of 6 hours, namely 5.66 %. The highest brightness test value was at a concentration of 0.8 % and a fermentation time of 24 hours, namely 63.4 %..